2010
DOI: 10.1002/elan.201000516
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry and Spectroscopy Study of In Vitro Interaction of Fenitrothion with DNA

Abstract: The interaction of Fenitrothion with DNA has been studied using the voltammetric and spectroscopic methods. An irreversible reduction was concluded from the CV data of Fenitrothion. The values of (an) , respectively. Also the voltammetric, spectroscopic, thermodynamic and activation energy of DNA-Fenitrothion complex revealed that the mode of interaction might be partial-intercalative and complex formation is entropy favored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 53 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that intercalators reduce EB‐DNA fluorescence by more than 50%, whereas the [compound]/[DNA] ratio ( r ) is below 100. [ 24,25 ] In this study, as the r increased from 0.028 to 0.2, and the EB‐DNA fluorescence decreased by approximately 75% for the compounds (Figure 8c and Table 1). These results indicate that BDPY‐4 and BDPY‐5 bind to DNA mainly through intercalative binding mode.…”
Section: Resultsmentioning
confidence: 58%
“…It has been reported that intercalators reduce EB‐DNA fluorescence by more than 50%, whereas the [compound]/[DNA] ratio ( r ) is below 100. [ 24,25 ] In this study, as the r increased from 0.028 to 0.2, and the EB‐DNA fluorescence decreased by approximately 75% for the compounds (Figure 8c and Table 1). These results indicate that BDPY‐4 and BDPY‐5 bind to DNA mainly through intercalative binding mode.…”
Section: Resultsmentioning
confidence: 58%
“…The negative value of the change in free energy of binding indicated the spontaneous nature of the process, hence suggests the toxic nature of the compound. However, a much smaller value as compared to other insecticides as reported in literature, [50–52] indicates lesser probability of the occurrence of the DNA‐PYR intercalation process and lesser toxicity as compared to conventional insecticides. Therefore, it can be concluded that PYR can be carcinogenic towards human if exposed at higher concentrations.…”
Section: Binding Studiesmentioning
confidence: 78%
“…-60C20 complex in different solvent mixtures was calculated by fitting the observed chemical shifts at various M 2? / 60C20 mol ratios with a nonlinear least-squares program in MATLAB (version 7.8) [22].…”
Section: Stability Constants Calculationsmentioning
confidence: 99%